Online Communities and Relationship Marketing : Concept and Empirical Investigation - Lim, Han Yuan (2003)
The idea of communication and network are playing an important role in the evolvement of the concept of marketing theories – from the marketing mix to relationship marketing. The development of technology, e.g. CRM seemed facilitating the dialogue, i.e. two-way communications between organizations and consumers in the consumer market. However, privacy concerns of consumers may destroy the relationships. Thus, online communities introduced in this dissertation could solve this problem, because the value of network of communication (i.e., information sharing, word-of-mouth communication, etc) can be achieved without the firm being locked out. Nevertheless, the appearance of “lurker”, participants who are watch or read but never have interaction within online communities, may cause losing value of online communities. Thus, to understand the reasons of consumers not having interaction within online communities is crucial. This research will come out the results of the question above.